2005
DOI: 10.1111/j.1528-1167.2005.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Absence Epilepsy: Evolution and Prognostic Factors

Abstract: Summary:Purpose: To evaluate how diagnostic criteria influence remission rates for patients with childhood absence epilepsy (CAE) and to assess clinical and EEG parameters as predictors of outcome.Methods: One hundred nineteen patients were diagnosed with CAE, according to International League Against Epilepsy (ILAE) classification criteria. They were subsequently evaluated according to stricter diagnostic criteria. Sixty-two subjects fulfilled these criteria as group 2; 57 did not and constituted group 1. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 24 publications
9
71
2
1
Order By: Relevance
“…6 Grosso et al demonstrated the strong influence of inclusion criteria on the outcome. 5 They classified patients with CAE into two groups, the first based on the ILAE classification 13 and the second on more strict criteria proposed by Loiseau & Panayiotopoulos. 2 The second group showed a higher rate of terminal remission defined as !…”
Section: Discussionmentioning
confidence: 99%
“…6 Grosso et al demonstrated the strong influence of inclusion criteria on the outcome. 5 They classified patients with CAE into two groups, the first based on the ILAE classification 13 and the second on more strict criteria proposed by Loiseau & Panayiotopoulos. 2 The second group showed a higher rate of terminal remission defined as !…”
Section: Discussionmentioning
confidence: 99%
“…Because these syndromes have relatively poor prognosis compared with CAE [40], their inaccurate categorization as CAE may lead to misrepresentation of the prognosis for CAE in clinical studies. Several studies using ILAE criteria reported the remission rate of CAE to be 50-60% [40][41][42]. To overcome these issues, we used stricter criteria than the ILAE ones to diagnose CAE in this study.…”
Section: Initial-response Group (N = 12)mentioning
confidence: 98%
“…Because of the relative laxity of the ILAE criteria, various types of generalized epilepsy syndromes with frequent absence seizures could be regarded as CAE [40]. Because these syndromes have relatively poor prognosis compared with CAE [40], their inaccurate categorization as CAE may lead to misrepresentation of the prognosis for CAE in clinical studies. Several studies using ILAE criteria reported the remission rate of CAE to be 50-60% [40][41][42].…”
Section: Initial-response Group (N = 12)mentioning
confidence: 98%
See 1 more Smart Citation
“…In childhood absence epilepsy, applying strict diagnostic criteria [29], 95% entered remission [30], while in juvenile absence epilepsy only 44% (8 out of 17) of seizures were controlled after the mean 6-year duration of follow-up [31]. Of patients with juvenile myoclonic epilepsy, 44-74% become seizure free on drug treatment [32][33][34].…”
Section: Seizure Type and Epilepsy Syndromementioning
confidence: 99%